DIAMOND DETECTORS FOR FAST TRANSIENT SCRAM MEASUREMENTS – THE DETECTOR DEVELOPMENT - Ondřej Novák; Lubomír Sklenka; Michal Pomorski; Clement Lynde (Acta Polytechnica CTU Proceedings)
This paper presents a development of special diamond detector for time dependent neutron flux measurements in a nuclear reactor. Neutron flux changes during SCRAM are difficult to measure by existing detector technologies. Therefore, a new detector is developed. This new type diamond based detector should allow to perform fast measurements of neutron flux during SCRAM with high pulse count rate. The diamond detector design and signal processing are described in this paper including the pulse shape discrimination method. In addition to theoretical detector study, three detector was manufactured at CEA Saclay. Experience gathered during manufacturing is described as well.